Continuous production of cellulose mixed esters via homogeneous reactive twin-screw extrusion catalyzed by ionic liquid - Hernandez, Stephanie C.; Milotskyi, Romain; Takagi, Shohei; Ito, Elisabeth R. D.; Suzuki, Shiori; Wada, Naoki; Takahashi, Kenji (Cellulose (London), 2023)
Cellulose mixed esters (CMEs) substituted with two different types of acyl groups are promising polymeric materials with various tunable properties but are arduous to produce. This is because of the insolubility of cellulose in common solvents, and thus, the industrial production of CMEs with desired degrees of substitution (DSs) requires a costly multistep process. To accomplish their facile production, homogeneous reactions have been performed using ionic liquids (ILs) as solvents for cellulose. However, the high viscosity of the cellulose-IL solutions causes insufficient mixing in batch reactors; thereby, favoring low cellulose concentrations with long reaction times (typically hours). Herein, we demonstrate a rapid and scalable production of CMEs by exploiting the excellent shear mixing of a twin-screw extruder as a flow reactor. A co-solvent system comprising an IL, 1-ethyl-3-methylimidazolium acetate, and dimethyl sulfoxide was applied to dissolve cellulose at a high concentration (15 wt.%) via twin-screw extrusion. During continuous extrusion at 80 °C, cellulose reacted with two acyl reagents, isopropenyl acetate (IPAc) and vinyl propionate (VPr) (2.5:0.5, mol/mol), to yield cellulose acetate propionate (CAP) within minutes. The CAP was stably produced during the operation time of 50 min with an average isolated yield of 71%. The DSs of the acetyl and propionyl groups of CAP were 1.77 and 0.50, respectively, corresponding to sufficiently high conversion rates of 70% for IPAc and 100% for VPr.